A Novel Sequential Approach for the Design of Heat Exchanger Networks - Caballero, Jose A.; Pavão, Leandro V.; Costa, Caliane B. B.; Ravagnani, Mauro A. S. S. (Frontiers in Chemical Engineering, 2021)
This paper presents a new algorithm for the design of Heat Exchanger Networks (HEN) that tries to take advantage of the strengths of the sequential and simultaneous approaches. It is divided in two sequential parts. The first one is an adaptation of the transportation model (TransHEN). It maintains the concept of temperature interval and considers the possibility of heat transfer between all the hot and cold streams inside those intervals, and at the same time it allows the a priori calculation of the logarithmic mean temperature difference between all possible heat exchanges, and therefore it maintains the area estimation linear in the model. The second step (HENDesign model) uses a superstructure that contains all the possible alternatives in which the matches predicted by the first stage model can exchange heat to design the final heat exchanger network. Unlike the sequential approach, in this model, we reoptimize all heat flows, temperatures, areas, etc. maintaining the set of matches predicted in the first stage. The model is highly nonlinear and nonconvex but it is relatively easy to get good results, because we start with the values predicted by the TransHEN model. We have tested the algorithm using fifteen benchmark problems to compare the performance of Heat Exchanger Network algorithms. In eleven out of the fifteen cases we obtained better or equal results than the best ones reported in the open literature. In three problems the results presented only marginal differences in total annualized cost (lower than 0.5 %) and only a difference of 2.4 % in the largest one.